2014
DOI: 10.1093/bja/aet485
|View full text |Cite
|
Sign up to set email alerts
|

Sufentanil administration guided by surgical pleth index vs standard practice during sevoflurane anaesthesia: a randomized controlled pilot study

Abstract: Sufentanil administration guided by SPI during sevoflurane anaesthesia is clinically feasible. In contrast to TIVA, it did not improve anaesthesia conduct with respect to unwanted somatic events, haemodynamic stability, sufentanil consumption, emergence time, or post-anaesthesia care unit care. Therefore, we conclude that anaesthesia regimen has an impact on beneficial effects by SPI guidance. Clinical trial registration NCT01525537. (Registered at Clinicaltrials.gov.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 29 publications
(48 reference statements)
2
62
1
3
Order By: Relevance
“…Although pre‐clinical and clinical (intra‐operative and postoperative) research indicated its ability to discriminate strong noxious stimuli from no stimulation , the method could not consistently differentiate stimulus intensities . The surgical plethysmographic index is not specific to nociception, and is influenced by both peripheral and central sympathetic tone , sex , intravascular volume status , heart rate , drugs , location of the probe , posture , levels of consciousness and in awake patients, pain anticipation and emotional stress. Although the non‐invasive nature of the clinical application is appealing, this is offset by large inter‐patient variability.…”
Section: Resultsmentioning
confidence: 98%
“…Although pre‐clinical and clinical (intra‐operative and postoperative) research indicated its ability to discriminate strong noxious stimuli from no stimulation , the method could not consistently differentiate stimulus intensities . The surgical plethysmographic index is not specific to nociception, and is influenced by both peripheral and central sympathetic tone , sex , intravascular volume status , heart rate , drugs , location of the probe , posture , levels of consciousness and in awake patients, pain anticipation and emotional stress. Although the non‐invasive nature of the clinical application is appealing, this is offset by large inter‐patient variability.…”
Section: Resultsmentioning
confidence: 98%
“…25, [6] In contrast, there are few reports of studies of other opioids administered via the intermittent bolus method for titration of analgesia by SPI guidance. [8] Gruenewald et al [8] reported that SPI-guided intermittent bolus administration of sufentanil was clinically feasible but was not able to significantly reduce intraoperative sufentanil consumption. However, the present study demonstrated that SPI-guided administration of intravenous oxycodone with an intermittent bolus dose can reduce cumulative oxycodone consumption during anesthesia without an increase in postoperative pain, compared with conventional analgesic practices, in patients undergoing thyroidectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Gruenewald et al [8] that used sufentanil as an analgesic and sevoflurane as a general anesthetic suggested that different anesthesia regimens have different impact on beneficial effects of SPI guidance, thereby raising questions over the efficacy of SPI guidance in anesthesia using volatile anesthetics in contrast to TIVA. In contrast, the present study indicated that SPI-guided oxycodone administration can provide effective analgesia during sevoflurane anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations